Deciphering the Interface of a High‐Voltage (5 V‐Class) Li‐Ion Battery Containing Additive‐Assisted Sulfolane‐Based Electrolyte. Issue 10 (6th September 2019) - Lu, Di; Xu, Gaojie; Hu, Zhiwei; Cui, Zili; Wang, Xiao; Li, Jiedong; Huang, Lang; Du, Xiaofan; Wang, Yantao; Ma, Jun; Lu, Xiaolan; Lin, Hong‐Ji; et al.
Abstract: Next generation high energy density lithium‐ion batteries have aroused great interests worldwide. Herein, in a high‐voltage (5 V‐class) LiNi0.5 Mn1.5 O4 /MCMB (graphitic mesocarbon microbeads) battery system using 1m lithium difluoro(oxalate)borate/sulfolane, tris(trimethylsilyl) phosphite (TMSP) additive is added to significantly improve room/high temperature cycling performances. The unchanged X‐ray diffraction patterns suggest the bulk crystal structure of cycled MCMB anode and LiNi0.5 Mn1.5 O4 cathode are well preserved. Moreover, soft X‐ray absorption spectroscopy (XAS) taken from bulk sensitive fluorescence‐yield (FY) mode reveals the unchanged bulk electronic structure of cycled LiNi0.5 Mn1.5 O4 cathode. Therefore, it is concluded that only interface instability contributes to capacity fading of full‐cells. However, electrode/electrolyte interface and corresponding interfacial reaction processes are always "enigmatic." First, X‐ray photoelectron spectroscopy (XPS) and in situ differential electrochemical mass spectrometry (DEMS) are used to more accurately decipher the TMSP additive action mechanism in MCMB/electrolyte interfacial reaction processes, by identifying the interfacial solid and gas byproducts, respectively. Then, the crucial role of TMSP additive in modifying cathode/electrolyte interface is revealed by XPS and soft XAS taken from surface sensitive total electron yield (TEY) mode. This paper provides valuable perspectives for formulating novel electrolytes, and for more accurately depicting additive action mechanism in "enigmatic" electrode/electrolyte interfacial reaction processes. Abstract : Here, a flame‐retardant and high thermal stability electrolyte of tris(trimethylsilyl) phosphite (TMSP) additive assisted 1m LiDFOB/SL is unprecedentedly proposed to enable excellent room/high temperature performances of a high voltage (5 V‐class) LiNi0.5 Mn1.5 O4 /MCMB battery. More importantly, advanced characterization techniques (such as X‐ray photoelectron spectroscopy (XPS), differential electrochemical mass spectrometry (DEMS), and X‐ray absorption spectroscopy (XAS)) are used to more accurately decipher additive action mechanism in the "enigmatic" electrode/electrolyte interfacial reaction processes.